1993
DOI: 10.1111/j.1749-7345.1993.tb00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Reproduction of the ShrimpPenaeus kerathurusHeld in Captivity

Abstract: The control of the reproductive cycle of the shrimp Penueus kerathurus, held in captivity from early juvenile stages without eyestalk ablation, was attempted in two sets of experimental conditions during two successive years. In the first set of experiments, light regime, sex ratio and presence of sand substratum were assessed in relation to ovarian maturation and successful mating. Examination of thelyca obtained from cast exoskeletons showed that 40–82% successful mating had taken place. A sex ratio of 2:l f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 11 publications
1
11
0
2
Order By: Relevance
“…Marsden et al (1997) also found that EPA did not contribute to reproductive output in Penaeus monodon. It may be that the EFA requirements of L. amboinensis were partly met by the C18 PUFAs, similar to the reports for other crustaceans (Luis and Ponte 1993;Cavalli et al 1999;Palacios et al 2001).…”
Section: Discussionsupporting
confidence: 81%
“…Marsden et al (1997) also found that EPA did not contribute to reproductive output in Penaeus monodon. It may be that the EFA requirements of L. amboinensis were partly met by the C18 PUFAs, similar to the reports for other crustaceans (Luis and Ponte 1993;Cavalli et al 1999;Palacios et al 2001).…”
Section: Discussionsupporting
confidence: 81%
“…Various essential FAs can impact on spawning quality; in M. rosenbergii increased dietary levels of LOA (ω-6 family) increased fecundity, measured as egg number per female weight (Cavalli et al 1999). Beneficial effects of high LOA on reproduction and offspring survival have also been reported for penaeids (Luis and Ponte 1993;Palacios et al 2001). A high concentration of C18 polyunsaturated fatty acids (PUFA) (including LOA) in the Artemia diet of L. amboinensis could be associated with high egg production, however, viable fecundity was low and may suggest a requirement for a different mix of FAs.…”
Section: Discussionmentioning
confidence: 97%
“…The feeding regime resulted in an increased number of eggs per spawning event for each female and increased egg viability and larval survival in shrimp (Briggs et al 1994) and more rapid maturation in cultured prawns (D'croz et al 1988, Luis & Ponte 1993 and sole (Diniz 1992). Nereidid worms contain large amount of essential PUFA, which allows broodstock conditioning for egg production by crustaceans (Lytle et al 1990, Olive et al 1992.…”
Section: Introductionmentioning
confidence: 99%